GAMBARAN TINGKAT PENGETAHUAN LANSIA TENTANG VAKSINASI COVID-19 DI DESA PASAR SENEN KECAMATAN AMBAL KABUPATEN KEBUMEN - Kusumaningsih, Tri Puspa; Elviyani, Riska (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
The age group most vulnerable to being affected by the COVID-19 disease is the elderly. Decreased immune system and comorbid diseases in the elderly increase the vulnerability of the elderly in the Covid-19 pandemic season. Based on the results of a preliminary study of 30 elderly people who were present at the Posyandu in Pasar Senen Village, they were asked questions about the covid-19 vaccine, there were 10 elderly people who did not know about the covid-19 vaccine. The purpose of this study was to determine the level of knowledge of the elderly about COVID-19 vaccination in Pasar Senen Village, Ambal District, Kebumen Regency. This research method is descriptive with a cross sectional approach. The population in this study were 224 elderly respondents and a sample of 74 respondents with accidental sampling. The measuring instrument uses a questionnaire. Data analysis using univariate. The results of the study The level of knowledge of the elderly about the covid-19 vaccine, namely 40 respondents (54.1%), only 19 respondents (25.7%), and 15 respondents less (20.3%). It is hoped that health workers will increase counseling about the COVID-19 vaccine among the elderly